A Randomised comparison and evaluation of I-gel, Supreme laryngeal mask airway and Ambu Auragain in Laparoscopic surgeries under general anaesthesia with controlled ventilation - Pradeep, Meenakshi Sumadevi; Nandanwankar, Niteen Khanderao; Lahane, Priya Vishwanath; Memon, Nazima Yusuf; Yennawar, Shridhar Devidas; Pathak, Ramesh Govindrao (Asian Journal of Medical Sciences, 2021)
Background: Supraglottic airway devices (SAD) are becoming increasingly popular for use in patients undergoing laparoscopic surgeries. In this prospective randomised study, we compared three supraglottic airway devices namely, I-gel, Supreme LMA and Ambu Auragain. Aims and Objectives: The study was undertaken to compare three supraglottic airway devices I-gel, Supreme LMA and Ambu Auragain in laparoscopic surgeries under general anaesthesia with controlled ventilation. Materials and Methods: This was a randomized comparative study in which 90 patients undergoing laparoscopic surgeries under general anesthesia were included. In group A Ambu AuraGain was used whereas in group I and Group S I-gel and Supreme LMA was used respectively. Primary outcome measures which were compared amongst the studied groups included time taken for insertion, ease of insertion, attempts required for insertion, ease of insertion of Ryles tube, fiberoptic bronchoscopic grading and Oropharyngeal leak pressure. Results: There was highly significant difference in the time taken for insertion of SAD in Group-A when compared to Group- I (p<0.0001) and Group-S (p<0.0001). Group-A had significantly increased grades of ease of insertion of SAD when compared to Group-I (p=0.04) and Group-S (p=0.004). 16.66% of patients in Group-A required 3 attempts for successful insertion of the SAD, while no patients in Group- I or Group A required more than two attempts for insertion(p<0.05). Conclusion: Ambu AuraGain provides better oropharyngeal seal and has higher leak pressures as compared to I-gel and Supreme LMA with similar hemodynamic stability and post-operative outcome makingit a preferable SAD over I-gel and Supreme LMA.